Knockdown of GINS2 inhibits proliferation and promotes apoptosis through the p53/GADD45A pathway in non-small-cell lung cancer. Issue 4 (3rd April 2020) - Chi, Feng; Wang, Zhou; Li, Yuzhu; Chang, Ning
Abstract: Lung cancer is a malignant tumour type with the highest morbidity and mortality, and non-small-cell lung cancer (NSCLC) is the most common pathological type. GINS complex subunit 2 (GINS2) is a member of the GINS family and is closely related to DNA replication and damage, participates in cell cycle regulation and plays a key role in cell proliferation and apoptosis. In the present study, we aimed to explore the role and underlying molecular mechanism of GINS2 in the development of NSCLC . The results showed that GINS2 is significantly increased in NSCLC tissues and cell lines. Knockdown of GINS2 significantly decreases cell proliferation, causing G2 /M phase cell cycle arrest. Knockdown of GINS2 reverses the effect of nocodazole on the levels of cyclin-dependent kinase 1 (CDK1) and cyclin-B1. Meanwhile, knockdown of GINS2 significantly elevates the apoptosis rate and apoptosis-related protein Bax and decreases Bcl-2. In addition, GINS2 knockdown induces an increase in the levels of p53 and growth arrest and DNA damage 45A (GADD45A). Co-transfection with GINS2-siRNA and siRNA against p53 (p53-siRNA) or co-transfection with GINS2-siRNA and siRNA against GADD45A (GADD45A-siRNA) partially reverses the effects of GINS2 knockdown on cell proliferation and apoptosis. Taken together, these results indicate that GINS2 knockdown down-regulates cell proliferation, induces G2/M phase cell cycle arrest and increases apoptosis, possibly through the p53/GADD45A pathway.